Antidepressant use and orthostatic hypotension in older adults living with mild‐to‐moderate Alzheimer disease. (3rd August 2020) - Dyer, Adam H; Murphy, Claire; Briggs, Robert; Lawlor, Brian; Kennelly, Sean P; ,
Abstract : Objectives: Antidepressant use is often reported as a risk factor for Orthostatic Hypotension (OH), however this relationship has never been explored in those with mild/moderate Alzheimer Disease (AD), who may represent a particularly vulnerable cohort. Methods: We performed a cross‐sectional analysis of baseline data from the NILVAD study. Participants with mild‐moderate AD were recruited from 23 centres in nine countries. Systolic and Diastolic Blood Pressure (SBP/DBP) was recorded in the seated position and after both 1 and 5 minutes of standing. OH was defined as a drop of ≥20 mmHg SBP/≥10 mmHg DBP. We examined the relationship between antidepressant use, orthostatic BP drop and the presence of OH, controlling for important covariates. Results: Of 509 participants (72.9 ± 8.3 years, 61.9% female), two‐fifths (39.1%; 199/509) were prescribed a regular antidepressant. Antidepressant use was associated with a significantly greater SBP and DBP drop at 5 minutes (β: 1.83, 0.16‐3.50, P = .03 for SBP; β: 1.13, 0.02‐2.25, P  < .05 for DBP). Selective Serotonin Reuptake Inhibitor (SSRI) use was associated with a significantly greater likelihood of OH (OR 2.0, 1.1‐3.6, P = .02). Both findings persisted following robust covariate adjustment. Conclusions: In older adults with AD, antidepressants were associated with a significantly greater SBP/DBP drop at 5 minutes. SSRI use in particular may be a risk factor for OH. This emphasises the need to screen older antidepressant users, and particularly those with AD, for ongoing orthostatic symptoms in order to reduce the risk of falls in this vulnerable cohort.